ANALISIS PAJAK PUSAT DAN DAERAH MELALUI PERSPEKTIF MAQASHID SYARIAH UNTUK MEWUJUDKAN KEADILAN SOSIAL EKONOMI - Allia Rosintan Siregar; Arifa Tussahidah; Hafidz Said Al Hudry Siregar (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study aims to analyze central and regional taxes through the perspective of maqashid sharia in realizing socio-economic justice in Indonesia. The research employs a descriptive qualitative approach using a library research method based on scientific journals, books, and relevant official documents on taxation and Islamic economics. The findings indicate that central and regional taxes play a crucial role as fiscal instruments in enhancing public welfare through income redistribution and development financing. However, the implementation of tax policies still faces several challenges, including low taxpayer compliance, lack of transparency, and unequal distribution of tax benefits. From the maqashid sharia perspective, tax policies should not only focus on state revenue but also emphasize justice, public benefit, and social balance. Therefore, integrating maqashid sharia values into tax management is essential to create a fair, transparent, and sustainable taxation system. This study is expected to contribute to the development of fiscal policies oriented toward overall societal welfare.